An Unusually Large Irritation Fibroma Associated with Gingiva of Lower Left Posterior Teeth Region - Ashish Lanjekar; Sunita Kulkarni; Sonali Akhade; Sonal Sonule; Usha Rathod (Case Reports in Dentistry)
Fibroma is a benign tumor of oral cavity, with usually the tongue, gingiva, and buccal mucosa being the most common sites. Females are twice more likely to develop fibroma than males. The intraoral fibroma typically is well demarcated; and its size can vary from millimeter to few centimeters. Intraorally the growth is attached to the mucosa by means of a peduncle. Fibroma is generally slow growing, painless, smooth surface lesion and the color is slightly paler than the adjacent healthy tissue. Treatment usually requires total excision and recurrence is rare. Here we present a case of 37-year-old female patient reported to the Department of Oral Medicine and Radiology with the chief complaint of a growth in the lower left posterior teeth region 3 months earlier.